2000
DOI: 10.1093/brain/123.6.1102
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune disease in first-degree relatives of patients with multiple sclerosis

Abstract: Previous studies examining an association with other autoimmune diseases have suggested the existence of a generalized autoimmune diathesis in patients with multiple sclerosis. We investigated the prevalence of autoimmune disease in first-degree relatives of probands with multiple sclerosis using a case-control method. The results show an excess of autoimmune disease within these families, but no significant association was seen with non-autoimmune diseases. The higher risk in multiplex than simplex families s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
116
2
9

Year Published

2002
2002
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(137 citation statements)
references
References 48 publications
10
116
2
9
Order By: Relevance
“…22 A number of investigators have suggested that some genetic factors influence susceptibility to a general autoimmune disease diathesis against which background additional genes determine which autoimmune condition develops. Studies showing increased prevalence of autoimmunity in first-degree relatives of multiple sclerosis patients 23 and a higher than expected concordance of linkage results across genome screens from different autoimmune diseases 24 support this hypothesis. A number of regions identified in our study overlap with those found in other autoimmune disease linkage screens.…”
Section: Discussionmentioning
confidence: 90%
“…22 A number of investigators have suggested that some genetic factors influence susceptibility to a general autoimmune disease diathesis against which background additional genes determine which autoimmune condition develops. Studies showing increased prevalence of autoimmunity in first-degree relatives of multiple sclerosis patients 23 and a higher than expected concordance of linkage results across genome screens from different autoimmune diseases 24 support this hypothesis. A number of regions identified in our study overlap with those found in other autoimmune disease linkage screens.…”
Section: Discussionmentioning
confidence: 90%
“…We did not find associations with any other specific autoimmune disorders, but even with an estimated 3100 total relatives in this study, we may not have had sufficient power to detect differences in the less common autoimmune disorders. The reports of an increased prevalence of AITD and other immune disorders among relatives of patients with rheumatoid arthritis (Walker, Griffiths, & Griffiths, 1986), Type I Diabetes (Payami, Joe, & Thomson, 1989), idiopathic inflammatory myopathy (Ginn et al, 1998), multiple sclerosis (Broadley, Deans Sawcer, Clayton, & Compston, 2000) and JRA (Prahalad, Shear, Thompson, Giannini, & Glass, 2002) have been interpreted as evidence for a common polygenic risk factor that confers susceptibility to autoimmunity (Ginn et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…143 Two studies have shown that psoriasis is more common in MS families than in controls. 129,130 Families with more than one case of MS had even higher odds of having psoriasis. Interestingly, while both are characterized by a Th-1 cytokine profile, MS appears to be exacerbated by TNF-alpha inhibition, an approach that is extremely effective in the treatment of psoriasis.…”
Section: Other Immune-mediated Diseasesmentioning
confidence: 98%
“…127 In addition to psoriatic arthritis, specific reports include an association of psoriasis with Crohn's disease. [128][129][130] In a series of case-control studies, 7-11% of those with Crohn's disease were diagnosed with psoriasis compared to 1-2% of controls. [131][132][133] Relatives of subjects diagnosed with either Crohn's or psoriasis also have been shown to have an increased incidence of having the other disease.…”
Section: Other Immune-mediated Diseasesmentioning
confidence: 99%